1968
DOI: 10.1139/o68-013
|View full text |Cite
|
Sign up to set email alerts
|

The chain termini of polynucleotides formed by limited enzymic fragmentation of wheat embryo ribosomal RNA. Part 1. Studies of snake venom phosphodiesterase

Abstract: The chain termini of polynucleotides formed by limited enzymic fragmentation of wheat embryo ribosomal RNA. Part 1. Studies of snake venom phosphodiesterase. Can. J. Biochem. 46, 81 (1968).Snake venom phosphodiesterase induces about fifteen exonucleolytic cleavages for each endonucleolytic cleavage during the first hour of hydrolysis sf wheat embryo ribosomal RNA, under the conditions of hydrolysis used in this present investigation. The polynucleotide chains in the sibosornaI RNA preparation have am average d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…More than 30 years ago, McLennan and Lane (76) inferred that W residues are probably concentrated at the junctions between single-stranded and helical regions in tRNA and rRNA. Detailed physicochemical studies (5,6) have now elucidated the consequences of such localization, since con rmed, in stabilizing higher-order structures.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 years ago, McLennan and Lane (76) inferred that W residues are probably concentrated at the junctions between single-stranded and helical regions in tRNA and rRNA. Detailed physicochemical studies (5,6) have now elucidated the consequences of such localization, since con rmed, in stabilizing higher-order structures.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little evidence in Figure 9 of further dephosphorylation to nucleoside. Several authors (Sulkowski et al, 1963;McLennan and Lane, 1968) have suspected that venom contains a phosphatase which is either specific for or highly preferential to nucleoside diphosphates. Present results support this contention.…”
Section: Discussionmentioning
confidence: 99%
“…Since the true chain lengths of wheat embryo 26S and 18S RNA are not known with certainiy at the present time, this assumed mass ratio may be high. On the other hand, it is known that under certain conditions wheat embryo 26S RNA can undergo a structural alteration with the formation of products the size of 18S RNA (McLennan and Lane, 1968). It has also been shown that wheat embryo NaCl-insoluble RNA contains a heterogeneous population of RNA species migrating on polyacrylamide gels between 26S RNA and 18S RNA and between 18S RNA and satellite RNA (Oakden et al, 1972), and accounting for about 25% of the mass of NaCl-insoluble RNA (Table VII).…”
Section: O1'-methylpseudouridine As a Component Of Wheatmentioning
confidence: 99%